Neuroimaging Pearls from the MDS Congress Video Challenge. Part 2: Acquired Disorders. Issue 3 (3rd February 2022) - Fearon, Conor; Rawal, Sapna; Olszewska, Diana; Alcaide‐Leon, Paula; Kern, Drew S.; Sharma, Soumya; Jaiswal, Shyam K.; Murthy, Jagarlapudi M.K.; Ha, Ainhi D.; Schwartz, Raymond S.; Fung, Victor S.C.; Spears, Chauncey; et al.
ABSTRACT: The MDS Video Challenge continues to be the one of most widely attended sessions at the International Congress. Although the primary focus of this event is the presentation of complex and challenging cases through videos, a number of cases over the years have also presented an unusual or important neuroimaging finding related to the case. We reviewed the previous Video Challenge cases and present here a selection of those cases which incorporated such imaging findings. We have compiled these "imaging pearls" into two anthologies. The first focuses on pearls where the underlying diagnosis was a genetic condition. This second anthology focuses on imaging pearls in cases where the underlying condition was acquired. For each case we present brief clinical details along with neuroimaging findings, the characteristic imaging findings of that disorder and, finally, the differential diagnosis for the imaging findings seen.